2013
DOI: 10.1371/journal.pone.0074795
|View full text |Cite
|
Sign up to set email alerts
|

Application of Quantitative MRI for Brain Tissue Segmentation at 1.5 T and 3.0 T Field Strengths

Abstract: BackgroundBrain tissue segmentation of white matter (WM), grey matter (GM), and cerebrospinal fluid (CSF) are important in neuroradiological applications. Quantitative Mri (qMRI) allows segmentation based on physical tissue properties, and the dependencies on MR scanner settings are removed. Brain tissue groups into clusters in the three dimensional space formed by the qMRI parameters R1, R2 and PD, and partial volume voxels are intermediate in this space. The qMRI parameters, however, depend on the main magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 35 publications
(64 reference statements)
5
40
0
Order By: Relevance
“…Patients in this cohort were newly diagnosed with possible MS or MS, and most were in the early stages of the disease. The ROC analysis gave a maximal AUC of 0.832, which is comparable with that in other studies, 15 This study was performed on a 1.5T scanner, and a previous study 27 has shown that the results of tissue segmentation from the qMRI sequence may differ between 1.5T and 3T. This means that the relaxation values of this study cannot be extrapolated to a 3T MR imaging setting.…”
Section: Discussionsupporting
confidence: 84%
“…Patients in this cohort were newly diagnosed with possible MS or MS, and most were in the early stages of the disease. The ROC analysis gave a maximal AUC of 0.832, which is comparable with that in other studies, 15 This study was performed on a 1.5T scanner, and a previous study 27 has shown that the results of tissue segmentation from the qMRI sequence may differ between 1.5T and 3T. This means that the relaxation values of this study cannot be extrapolated to a 3T MR imaging setting.…”
Section: Discussionsupporting
confidence: 84%
“…If the same method had been applied using different MRI scanners, values presented here represents the mean from those measurements [18]. …”
Section: Methodsmentioning
confidence: 99%
“…4,5 The quantitative nature of the method and its ability to probe multiple physical properties in a single sequence make it suitable for volumetric analysis. [6][7][8][9][10] Synthetic MR imaging has shown promising initial results for use in MS and patients with an ischemic event. 11,12 The technique is consequently gaining interest as a potentially time-efficient alternative to conventional MR imaging to visualize and quantify brain tissue properties.…”
mentioning
confidence: 99%